Assessing Couples’ Readiness and Child’s Best Interests: A Comparative Analysis of Mojokerto Religious Court Decisions on Marriage Dispensation - Arif, Alfiyah Faizatul (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2025)
The issue of marriage dispensation (dispensasi nikah) continues to attract significant scholarly attention in Indonesia, especially after the legal reform that raised the minimum marriage age to 19 for both men and women. This change has led to an increase in dispensation requests submitted to religious courts, where judges have the discretionary power to approve or reject each case based on its unique circumstances. This article analyzes two contrasting rulings from the Mojokerto Religious Court—Case Number 321/Pdt.P/2024/PA.Mr and Case Number 597/Pdt.P/2024/PA.Mr—both filed due to pregnancy outside marriage. Despite similar legal grounds, the court granted the petition in the first case but denied it in the second. Using a normative legal approach that combines statutory and philosophical perspectives alongside legal interpretation theory, the study reveals that both decisions employed teleological reasoning. However, judges assessed the couples’ readiness for marriage differently, taking into account psychological, social, and economic factors. In Case 321, with a 15-week pregnancy, the applicants were deemed ready, while in Case 597, involving a 12-week pregnancy, they were not. Both rulings relied heavily on recommendations from the Integrated Service Center for the Empowerment of Women and Children (P2TP2A). While judges emphasized the child’s best interests, the analysis highlights a tendency to prioritize institutional opinions over independent judicial reasoning (ijtihād). This raises important questions about the extent to which human rights considerations are deeply engaged in contemporary Islamic family law decisions in Indonesian religious courts.